IMPLEMENTASI KEGIATAN OLAHRAGA ADAPTIF DALAM MENINGKATKAN KEMANDIRIAN DAN PERCAYA DIRI SISWA TUNADAKSA - Khalisa Hairani Harahap; Mhd Fadhlul Hidayat; Refina Jiska Adelia, Rassya Nayla Ruliansyah; Yan Indra Siregar, Ahmad Syabaruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of adaptive sports activities in enhancing independence and self-confidence among students with physical disabilities (tunedaksa). Using a qualitative descriptive method, data were collected through observations, in-depth interviews, and documentation involving physical education teachers, students, and parents in an inclusive school setting. The findings reveal that adaptive sports activities tailored to the physical abilities and individual needs of students effectively promote active participation, courage to try new things, and decision-making skills. Furthermore, structured physical activities positively impact students' self-confidence, especially in social interactions and self-acceptance. Key supporting factors include teacher support, availability of assistive tools, and a supportive inclusive environment. The study recommends ongoing training for teachers and sustainable development of adaptive sports programs to optimally support the psychosocial development of students with physical disabilities.